The Use of Talking Chips Technique in Students' Impromptu Speaking - Syaripudin, Usep; Nuristiana, Pia (Universitas Swadaya Gunung Jati, 2014)
The purpose of learning language is to communicate with people. It means that speaking is one important skill in learning language. Based on pre-observation, students encountered many problems, such as lack of vocabularies, grammar, fluency and pronunciation. Therefore, the writer wanted to solve those problems by using Talking Chips technique in teaching speaking. The aims of the study were to find out the data of the use of Talking Chips technique affects students or not, and to find out the students' responses about Talking Chips technique in speaking class. The subject of this study was the First Year in University in Cirebon. The total sample was fourty students. This study used quasi experimental design with control class. In experimental class, the class which used Talking Chips technique in teaching speaking, it was conducted in three steps, such as pre-test, treatments, and post-test. The findings of this study were that Talking Chips technique is effective to students' speaking ability, especially in impromptu speaking. By comparing the mean score of experimental and control class, it was found that the Talking Chips technique is effective in teaching speaking. From the data, it can be concluded that many students spoke in English very often therefore the students got higher scores. It was supported by the data of questionnaire of students' responses. Those responses said that Talking Chips gives many benefits to foster students' speaking ability.